Synthetic playing surfaces increase the incidence of match injuries in an elite Rugby Union team - Cousins, B. E.W.; Morris, J. G.; Sunderland, C.; Bennett, A. M.; Shahtahmassebi, G.; Cooper, S. B. (Journal of Science and Medicine in Sport, 2022)
Objectives: To examine differences in match injury incidence between three playing surfaces in elite Rugby Union. Design: Prospective cohort. Methods: Match injury incidence was assessed in 89 elite Rugby Union players over two-seasons of professional competition (44 matches, 1014 h player exposure). Match injury incidence was assessed on three different playing surfaces; natural grass, hybrid (natural grass combined with approximately 3% synthetic fibres) and fully synthetic (sand and rubber infill). Overall injury incidence, contact and non-contact injury incidence, and the incidence of minor (=7 d lost) and major (=8 d lost) injuries were considered using mixed effect models. Results: Overall match injury incidence doubled on hybrid and synthetic surfaces compared to natural grass (hybrid: OR = 2.58 [95% CI 1.65-4.03], p < 0.001; synthetic: OR = 2.16 [95% CI 1.07-4.37], p = 0.033). Furthermore, the odds of sustaining a contact injury on a pitch containing any synthetic content also increased compared to natural grass (hybrid: OR = 2.31 [95% CI 1.41-3.78], p = 0.001; synthetic: OR = 2.19 [95% CI 1.00-4.77], p = 0.049). The hybrid surface elicited a four times greater likelihood of non-contact injury incidence compared to natural grass (OR = 4.18 [95% CI 1.16-15.04], p = 0.028). However, the playing surface did not affect the severity of match injuries (all p > 0.05). Conclusions: The present study suggests that even a small percentage (3%) of synthetic content in the playing surface significantly increases match injury incidence, with an effect seen on both contact and non-contact injury incidence. These findings are important to enable practitioners to be aware of the injury implications of playing matches on hybrid and synthetic pitches.